COVID-19 associated reduction in elective spay-neuter surgeries for dogs and cats - Guerios, Simone D.; Porcher, Tenley R.; Clemmer, Gina; Denagamage, Thomas; Levy, Julie K. (Frontiers in Veterinary Science, 2022)
The rise in subsidized spay-neuter access helped drive the euthanasia of shelter pets in the US from an estimated 13.5 million in 1973 to 1.5 million in 2019. When the arrival of the COVID-19 pandemic triggered lockdowns beginning in March 2020, many veterinary providers suspended nonessential services such as routine spay-neuter surgeries. The purpose of this study was to determine the impact of the COVID-19 pandemic on the volume of spay-neuter procedures performed by spay-neuter clinics. A retrospective study of patient data from 212 spay-neuter clinics using Clinic HQ practice management software was conducted from January 2019 through December 2021. The clinics collectively performed 1,217,240 surgeries in the pre-COVID baseline year of 2019. A sharp decline in surgeries began in March 2020 (-22%) and reached a nadir in April 2020 (-80%). Surgeries began to increase in May 2020 (-39%), before plateauing in July 2020 (-6%) and remaining slightly below the 2019 baseline in most months through the end of 2021. Compared to 2019, total surgeries decreased 13% to 1,059,388 in 2020 and decreased 3% to 1,184,274 in 2021. In 2020, when clinic disruptions were highest, the impact of the surgery cutbacks varied by geographic region, species, age, and source of animals. Compared with 2019, in 2020 surgeries decreased 17% in the Midwest region, 15% in the Northeast and West, and 11% in the South. Surgeries were reduced 19% in dogs and 10% in cats. When grouped by age, surgeries were reduced by 18% in geriatrics, 14% in adults, and 11% in juveniles. Reductions were similar for females (-14%) and males (-12%) and similar for unowned/organization-owned animals (-14%) and privately owned animals (-12%). In total, 190,818 fewer surgeries were performed by the 212 studied clinics in the 24 months from January 2020 through December 2021 than would be expected had 2019 levels been maintained. If a similar pattern was experienced by other spay/neuter providers in the US, it would suggest there is a deficit of more than 2.7 million spay/neuter surgeries that animal welfare organizations have yet to address.